A novel mutation in SLC1A3 causes episodic ataxia. Issue 2 (February 2018) - Iwama, Kazuhiro; Iwata, Aya; Shiina, Masaaki; Mitsuhashi, Satomi; Miyatake, Satoko; Takata, Atsushi; Miyake, Noriko; Ogata, Kazuhiro; Ito, Shuichi; Mizuguchi, Takeshi; Matsumoto, Naomichi
Abstract Episodic ataxias (EAs) are rare channelopathies characterized by recurrent ataxia and vertigo, having eight subtypes. Mutated genes were found in four of these eight subtypes (EA1, EA2, EA5, and EA6). To date, only four missense mutations in the Solute Carrier Family 1 Member 3 gene (SLC1A3 ) have been reported to cause EA6.SLC1A3 encodes excitatory amino-acid transporter 1, which is a trimeric transmembrane protein responsible for glutamate transport in the synaptic cleft. In this study, we found a novel missense mutation, c.383T>G (p.Met128Arg) inSLC1A3, in an EA patient by whole-exome sequencing. The modeled structural analysis suggested that p.Met128Arg may affect the hydrophobic transmembrane environment and protein function. Analysis of the pathogenicity of all mutations found inSLC1A3 to date using multiple prediction tools showed some advantage of using the Mendelian Clinically Applicable Pathogenicity (M-CAP) score. Various types ofSLC1A3 variants, including nonsense mutations and indels, in the ExAC database suggest that the loss-of-function mechanism bySLC1A3 mutations is unlikely in EA6. The current mutation (p.Med128Arg) presumably has a gain-of-function effect as described in a previous report.